Sustainability of 3D Modular Steel Intensive Building for Students’ Residence - Monteiro, Safira (2016)
Currently, there is an increasing concern about the seriousness of global intensive use of energy and consequent deterioration of the environment. This concern has led to the improvement of the pillars of sustainable development in the last decades. The construction sector presents one of the biggest challenges in the past. The construction, fit-out, operation and the final demolition of buildings contributes to a large-scale negative impacts on the environment, even at the level of material and energy consumption, or even because the inefficient structure. (Sandy Halliday, 2008)This document is based on a thorough study that encompasses the design phase, construction, use and, finally, end-of-life of a modular building, which will be placed in Luleå, Sweden.The study was performed based on research methods, calculation and software of design and energy. The aim of this study is to analyze the sustainability of the future building, first from an energy point of view, so as to know the specific energy consumption, and on the other hand from an environmental stand point by leading a complete life-cycle assessment (cradle-to-grave).To complete the study a background of the situation relating to the sustainability theme I provided.The results obtained from this current work aim to help in the selection of better materials for isolation, better systems of ventilation, heating and cooling in order to reach the energy values demanded by law for domestic consumptions. These same results will dictate the validation of the building inside of the required norms.The research is part of project FRAMEUP, project RFCS that includes the University of Technology of Luleå, RWTH Aachen, University of Liège, University of Coimbra and also three companies, Part AB, Sweden, Acciona, Spain and Vallourec & Mannesmann, Deutchland. Validerat; 20160331 (global_studentproject_submitter)